Algoritmo Corea: una premessa - Matteo Casari (Antropologia e Teatro)
The dossier Algoritmo Corea: performing arts ai tempi dell’intelligenza artificiale [Algorithm Korea: Performing Arts in the Age of Artificial Intelligence] explores the intersection of performing arts, technology, and artificial intelligence within the context of South Korea, a country renowned for its prominent role in technological advancements and cultural industries. Through an extensive analysis, the work aims to provide a historical and anthropological overview of the relationships between art and technology, highlighting how Korean performing arts reflect and critically engage with technological progress and its cultural impacts. The dossier serves as an entry point into Korean culture and theater, offering a thoughtful reflection on the use of advanced technologies in the arts and suggesting interpretive frameworks to understand a rapidly evolving present, where South Korea emerges as a global leader.